TRANSHUMANISM IN THE PERSPECTIVE OF PHILOSOPHICAL AND RELIGIOUSANTHROPOLOGY - Konotop, Lyudmyla (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The article is devoted to the philosophical, religious understanding of the latest technologies in the field of natural sciences. We are talking about transhumanism, which causes a number of problems – genetic engineering, biotechnology, related to the philosophical justification of ethical provisions pro et contra, and research in neurobiology and cybernetics, with the prospect of changes in the human brain, creative and semantic abilities, related to philosophical and religious discussions about the nature of consciousness and intellect. The aim and tasks of the article is to justify and disclose the main characteristics of transhumanism not only as a specific scientific field, but also as a big problem of ethics. The main aim is a research, analysis, disclosure and explanation of the essential characteristics of transhumanism, its connection with all spheres of society, with the basics of human life. Research methods of trans-humanism in particular are systemic, interdisciplinary, analytical, hermeneutical, historical and philological methods, the method of innovative ethnography, etc. Religion exists and functions in a particular society, in a particular sociocultural and the political situation, therefore, one of the methods of studying transhumanismis the comparative method includes this entire multicomponent. Research results. The basic conceptual values of transhumanism are revealed, which are formulated regardless of the historical context of a certain era. It is emphasized that trans-humanism as a worldview can have meanings if the ethical principles of using its technological aspects are resolved. Religion, which considers most artificial technologies to be purely negative, plays a role in resolving the moral rationale for trans-humanism. Discussion says that methodological integration involves a systematic, typological, comparative and field study of trans-humanism. Conclusion.The conclusion is that the universal practical and immoral goal of transhumanism is to achieve power over all characteristics of human life.